Indonesia consumer preferences on attributes of marketplace platform: a conjoint analysis approach - Satria Fadil Persada; Reny Nadlifatin; Angelica Cintya Mannuela Wibowo; Etsa Astridya Setiyati; Prawira Fajarindra Belgiawan; Yogi Tri Prasetyo; Ardvin Kester S. Ong; Michael Nayat Young (Cogent Business & Management, 2024)
The goal of this study is to find out what combination and number of features people prefer when selecting a marketplace platform. This study's target objects are marketplace platforms, which are among the top three most used by Indonesians. Conjoint analysis is used to assess consumer preferences using specified marketplace attributes. Platform view, promo, payment method, marketplace type, delivery services, and reviews are the stated attributes. Non-probability purposive sampling techniques were used to acquire data on early 2023 and 100 respondents were participated. This is accomplished by providing questionnaires using online forms to Indonesian students who utilize the marketplace platform. This last research will determine the combination and level of qualities that students desire when selecting a marketplace platform. The payment method attribute was discovered to be the most influential on student preferences. The second attribute is marketplace, followed by promotions, delivery services, reviews, and platform appearance. Several ideas and techniques were shared.
Keywords: 650; attribute; conjoint analysis; Consumers; marketplace; preferences